Implementasi Living Quran: Pembelajaran al-Quran bagi Lansia di Masjid Baitul Amin Sleman Yogyakarta - Syihabudin, Moh. Nizar (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: The aim of this research is to determine the form of implementation of the Living Quran concept in the process of learning to read and understand the Koran for the elderly at the Baitul Amin Mosque, Sleman Yogyakarta. This research uses a descriptive qualitative approach by triangulating data, namely direct observation and interviews with competent informants and carrying out documentation. Data analysis techniques use interactive models. There are four stages that researchers must go through, namely data reduction, data presentation and drawing conclusions. The research results show that the level of ability to read the Koran in the Mundu Sleman community, especially among the elderly, is still relatively low. This also happens with a lack of religious understanding. Therefore, the concept of Living Quran emerged at the Baitul Amin Mosque, Sleman, Yogyakarta, which implements learning to read the Koran, thematic studies, and the formation of home study groups. Various obstacles arise from internal and external factors. However, total support from the Takmir Mosque management and the motivation of the elderly were able to minimize all existing obstacles so that the Living Quran program could run smoothly and be able to achieve the expected goals.